Effects of a Clinical Decision-Making Program on Medication Safety Competency among Advanced-Beginner Nurses in Intensive Care Units: A Nonequivalent Control Group Pretest–Posttest Study with a Time-Lagged Design - Se Yeong Park; Hea Kung Hur (Korean Journal of Adult Nursing, 2026)
Purpose: This study evaluated the immediate and sustained effects of a clinical decision-making program based on Simon’s decision-making model on medication safety competency among advanced-beginner nurses in intensive care units. Methods: This nonequivalent control group pretest-posttest study used a time-lagged design and included 18 intensive care unit nurses at a tertiary hospital, with 12 assigned to the intervention group and six to the control group. The intervention group participated in a 2-week clinical decision-making program that integrated case-based learning and high-fidelity simulation, whereas the control group received lecture-based education. Clinical decision-making ability, medication safety competency, and safety motivation were measured at baseline and at 2 and 4 weeks after baseline. Near-miss medication error experiences were assessed at baseline and at 4 and 10 weeks. Data were analyzed using the independent t-test, Mann-Whitney U test, and linear mixed models. Results: Clinical decision-making ability (F=3.94, p=.026), medication safety competency (F=4.97, p=.011), safety motivation (F=5.20, p=.009), and near-miss medication error experiences (F=14.28, p